MODE OF COLLAPSE OF SQUARE SINGLE PANEL REINFORCED CONCRETE SPACE- FRAMED STRUCTURES WITH RIGID BEAM-COLUMN JOINTS (Nigerian Journal of Technology, 2015)
The behavior of the structural elements of a space-framed structure depends on their support conditions. These support conditions can be hinged or rigid for beam-column joints, while for slab these support conditions can be simply supported on walls that are not monolithically constructed together, simply supported on beams that are monolithically constructed together and, can be freely supported on one, two or three edges. This paper studies the mode of collapse of collapse of a single-paneled reinforced concrete space-framed structure with rigid beam-column joints. Five models were investigated for the interactive behavior of slabs, beams and columns. The models were loaded directly till collapse. The estimated and actual collapse loads of the five models were compared. The estimated collapse load for the slab was 35 kN/m2. Also, the numerical estimate of the collapse load for the beam was 10.2kN/m (with an equivalent slab load of 40.8kN/m2), while the shear capacity at the beam-column joints was estimated to be 19.14 kN. The mode of collapse for all the five models was by shear failure at the beam-column joints at an average shear force of 7.13 kN as against the estimated shear capacities of 19.14 kN,  showing that the existing formulae for predicting shear capacity of beam-column joints gave an overestimated value of joint shear capacity up to about 168%. It was found that the space framed models failed by shearing at the beam-column joints, and that the estimated shear capacity was greater than the shear force at collapse.  http://dx.doi.org/10.4314/njt.v35i1.3